2012
DOI: 10.1007/s00167-012-2260-7
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ACL remnants in knee stability

Abstract: Prognostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Based on arthroscopy, it is however possible to differentiate partial tears (the antero-medial bundle being more often concerned than the posterolateral one) from complete ACL lesions presenting either as a totally resorbed ligament or as a healed remnant on the intercondylar notch or the PCL [78]. These different lesions influence the SSD observed in anterior and rotational knee laxity measurements [76,[79][80][81][82]. As such, only considering complete tears to evaluate the diagnostic performance of an arthrometer cannot reflect its true diagnostic capacity.…”
Section: Further Considerations For Diagnosismentioning
confidence: 99%
“…Based on arthroscopy, it is however possible to differentiate partial tears (the antero-medial bundle being more often concerned than the posterolateral one) from complete ACL lesions presenting either as a totally resorbed ligament or as a healed remnant on the intercondylar notch or the PCL [78]. These different lesions influence the SSD observed in anterior and rotational knee laxity measurements [76,[79][80][81][82]. As such, only considering complete tears to evaluate the diagnostic performance of an arthrometer cannot reflect its true diagnostic capacity.…”
Section: Further Considerations For Diagnosismentioning
confidence: 99%
“…Crain et al 2 reported that there were no changes in the anteroposterior laxity of the knee after remnant debridement for cases with absent or PCL-adhering remnants, whereas cases with roof-or wall-adhering remnants showed increased instability after debridement. Nakase et al 6 reported that cases with the remnant attached to the lateral wall affects not only the anteroposterior laxity but also the rotational stability of the knee. In addition, Nakamae et al 7 reported that there was increased laxity for those who underwent remnant removal within 1 year of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Proprioception is a key factor in maintaining the stability of the knee joint against functional de ciencies after ACL reconstruction. Many mechanoreceptors known to be distributed in ACL and remnant tissues contribute to the proprioceptive function of the knee [13,14]. Some previous studies have reported the presence of mechanoreceptors in ACL remnants after ACL reconstruction with the remnant preservation technique [5,15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated proprioception, as well as the function of mechanoreceptors in reconstructed ACLs [5,10,13,14,15,16,17]. However, it is di cult to compare outcomes between these studies because of variations in the experimental methods and other external factors.…”
Section: Discussionmentioning
confidence: 99%